Pengembangan Aplikasi Tour Guide Wisatawan Berbasis Android Menggunakan Gps - Zendy Saputra; Shofiya Syidada; Anang Kukuh Adisusilo (Informatics Engineering Department-UWKS, 2016)
Tourism is a thing that is now developing in Indonesia, including in the city of Nganjuk. Nganjuk city since the first is already famous for its tourism mascot that is Niagara Sedudo and muddy ric e in distinctive food, but the food typical tourist attraction and other less known by tourists because of the lack of information that was obtained. In this study, will be made an application to introduce the city Nganjuk with apikasi as a Tour Guide.The introduction consists of the attractions and culinary in Nganjuk city consisting of details of tourist attractions and specialties, maps, and gallery. This application uses the Google Maps API to display maps and routes from somewhere and Global Positioning System (GPS) to determine the position of the current user. Along with advances in technology, this application is made on Android -based mobile device so it's easy to be accessed anywhere and anytime as long as have an internet connection. From the test results applications can run well to show the route of travel, gallery shows, listen to the sound in Android Kitkat.